Oral Motor Exercise in Improving the Movements Of The Jaw, Lip, Tongue in Case of Oral Phase Dysphagia on a Cerebral Palsy Patient - Yosrika Yosrika; Riani Sophianti; Karmilah Karmilah (International Journal of Quantitative Research and Modeling, 2023)
The dysphagia case in children with cerebral palsy is a disorder that must be treated immediately because it will have a serious impact on the child's health and speech fluency. The Oral motor exercise method is one of the therapies to improve jaw, neck, and tongue movements in patients with cerebral palsy. The purpose of this study was to investigate the oral motor exercise on a dysphagia patient of  3-years old   with cerebral palsy disorder at Syamsudin SH Hospital, Sukabumi,  from January to March 2019. This type of research is a descriptive quantitative method with single subject experiment.  A research subject was  a patient with cerebral palsy, a 3- years old – boy who has dysphagia. The patient cannot speak and only cries and says 'AAAA' if he wanted something and the patient was choking and coughing when eating or drinking. To deal with this problem, 20 sessions of therapy and 1 evaluation were carried out. The results showed that by comparing the results of the initial test and the final test, there was an increase in the ability to move the organs of the lips, tongue, jaw, and chewing movements of the patient. In the initial test, the patient got 2 points and the final test result. the patient got 4 points which indicated 50% success scale. From the therapeutic success scale obtained, it was concluded that the therapy was quite successful.